Il governo del territorio e del paesaggio rurale nello spazio “terzo” periurbano. Il parco agricolo come strumento di politiche e di progetto - Fanfani, David (Ri-Vista. Research for landscape architecture, 2006)
The recent transformations and evolution of the urban and metropolitan systems in Europe, as well as in Italy, have often produced settlements forms where the edge between urban ad rural spaces goes to fade and where the legacy of the rural society and of the agricultural landscape is often eroded under the urban equipments and housing development pressure. Nevertheless in such as settlements the role of the open spaces remains still pivotal. Infact they can provide very helpful “public goods” - as such as urban ecosystem and urban-rural landscapequality-and -atthesametime-goods,facilitiesandamenitiesfortheurbanpeople–assuchasshort foods supply chain, recreational, tourist, social and cultural services. For planning agenda facing this context of mingled urban-rural patterns and functions means to deal with new planning and governance strategies. Agricultural park device seems to fit with the problems at stake. In many cases in Europe and Italy it permits to pursue the multifunctional and integrated goals for managing the periuban places and to set up the operational framework to develop territory and landscape designs aimed to protect and, sometimes, recreate the identitary, environmental, social and economic values of the open spaces.